Historia de las mujeres y memoria histórica: Manuela Sáenz interpela a Simón Bolívar (1822-1830) - Vilalta, María José (European Review of Latin American and Caribbean Studies, 2012)
Abstract: Women's history and historical memory: Manuela Sáenz addresses Simón Bolívar (1822-1830)In the construction of women's history, it is necessary to thoroughly review the manipulations of memory concerning the feminine presence, whether hidden or visible, in all historical and present-day societies. The widely divergent interpretations of a female icon, Manuela Sáenz – the most famous lover of Simón Bolívar – are a paradigmatic example that allows us to reflect on specific themes from a much broader perspective.Resumen:En la construcción de la historia de las mujeres, es necesario revisar a fondo las manipulaciones de la memoria sobre la presencia femenina, ya sea oculta o visible, en todas las sociedades históricas y actuales. Las interpretaciones muy divergentes de un icono femenino, Manuela Sáenz – la más famosa amante de Simón Bolívar – son un ejemplo paradigmático que nos permite reflexionar, desde lo particular, sobre temas de ámbito más general.